2006
DOI: 10.1073/pnas.0608849103
|View full text |Cite
|
Sign up to set email alerts
|

The gatekeeper residue controls autoactivation of ERK2 via a pathway of intramolecular connectivity

Abstract: Studies of protein kinases have identified a ''gatekeeper'' residue, which confers selectivity for binding nucleotides and small-molecule inhibitors. We report that, in the MAP kinase ERK2, mutations at the gatekeeper residue unexpectedly lead to autoactivation due to enhanced autophosphorylation of regulatory Tyr and Thr sites within the activation lip that control kinase activity. This occurs through an intramolecular mechanism, indicating that the gatekeeper residue indirectly constrains flexibility at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
124
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(133 citation statements)
references
References 33 publications
6
124
2
Order By: Relevance
“…A number of drug-resistant kinase mutants with altered gatekeeper residues have been identified in multiple kinases that have been effectively targeted clinically: BCR-Abl (T 315I ), EGFR (T 790M ), KIT (T 670I ), and ALK (L 1196M ). Mutation of the gatekeeper residue in rat ERK2 (ERK2 Q103 ) to glycine or alanine has been shown to increase autoactivation by enhancing autophosphorylation of the Thr 183 and Tyr 185 in the activation loop (32). Exploring this further, we found that mutation of human ERK2 glutamine 105 to glutamic acid (Q 105E ) was sufficient to mediate resistance in the presence of an ERK inhibitor through mechanisms that are not fully defined (data not shown).…”
Section: Discussionmentioning
confidence: 74%
“…A number of drug-resistant kinase mutants with altered gatekeeper residues have been identified in multiple kinases that have been effectively targeted clinically: BCR-Abl (T 315I ), EGFR (T 790M ), KIT (T 670I ), and ALK (L 1196M ). Mutation of the gatekeeper residue in rat ERK2 (ERK2 Q103 ) to glycine or alanine has been shown to increase autoactivation by enhancing autophosphorylation of the Thr 183 and Tyr 185 in the activation loop (32). Exploring this further, we found that mutation of human ERK2 glutamine 105 to glutamic acid (Q 105E ) was sufficient to mediate resistance in the presence of an ERK inhibitor through mechanisms that are not fully defined (data not shown).…”
Section: Discussionmentioning
confidence: 74%
“…The buffer used for ERK2 in NMR experiments contained 50 mM Tris (pH 7.4), 150 mM NaCl, 5 mM MgSO 4 , 0.1 mM EDTA, 5 mM DTT, 100% D 2 O, and 2.5% (vol/vol) glycerol. Kinase activities of 0P-ERK2, ME/GG-ERK2, and 2P-ERK2 were measured as described in a previous study (36). Nucleotide binding experiments were performed by titrating AMP-PNP (Roche Applied Science) into the NMR samples of 0P-ERK2 and 2P-ERK2, to final AMP-PNP concentrations of 1.35 mM and 1.15 mM, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Hydrogen-deuterium exchange coupled to mass spectrometric (HDX-MS) analysis provides an alternative approach to determining ligand-linked structural and/or dynamic changes in the BirA monomer (19,20). This method has proven powerful in localizing changes in the levels and rates of peptide backbone H-D exchange in proteins as they form complexes and it has been successfully applied to analyzing the allosteric response in several protein systems (21)(22)(23)(24). Its major advantage over other techniques for analyzing the allosteric response in BirA is that the exchange can be performed at concentrations at which even the liganded forms of BirA are predominantly monomeric.…”
Section: The Biotin Repressor: An Allosteric Site-specific Dna Bindinmentioning
confidence: 99%